Influence of Physical and Chemical Soil Properties on the Adsorption of Escherichia coli in Mollisols and Alfisols of Argentina. - Behrends Kraemer, Filipe (2013)
Bacterial adsorption on soils and sediments is one of the main factors that control bacterial transport to water bodies. In this work, 32 soil samples representative of the most important arable areas of the Rolling Pampa region (Argiudolls) and bottomlands devoted to livestock production (Natraqualfs) were analyzed in order to evaluate bacterial-soil adsorption. The first axis of a principal component analysis explained 45% of the total variation among soils in 11 physical and chemical properties, and was strongly and positively related to bacterial adsorption (r2=0.67). Soil bacterial adsorption presented a large range of values (25-73%), being those for Argiudolls significantly higher than those for Natraqualfs. For both soils, cation exchange capacity (CEC) (r2=0.67) and clay content (r2=0.55) were positively associated with bacterial adsorption; whereas exchangeable sodium percentage (ESP) showed a negative tendency (r2=0.42). It is concluded that in the basin studied, granulometry, CEC and ESP proved to be important properties to discriminate bacterial-soil adsorption, and the following equation to estimate mean soil bacterial adsorption in these soils is proposed: y=1.73×CEC ? 0.05×sand(50-250 μm)[g kg?1]?0.54×ESP (R2adjust=0.77). These results would help to monitor water quality of surface water bodies by the development of bacterial transport models using standard soil data.